What Do Leaders Need to Know About Leadership Shelf Life? (Journal of Leadership, Accountability and Ethics, 2022)
Leadership scholars have studied the concept for over 150 years. They have generally focused on how prospective leaders can prepare, and later emerge into leadership roles. Others have focused on leadership practices that success in the role. Very few scholars have focused on the inevitable reality of leaving a leadership role. Leaders in all areas of endeavour have a shelf life and will eventually leave the role. The authors of this manuscript discuss the concept of leadership shelf life and provide current and aspiring leaders with 10 implications to help them recognize leadership shelf-life issues, facilitate leader renewal, and, when appropriate, help them effectively exit the leadership role with their dignity intact and the unit poised for sustained success.
Keywords: leadership; accountability; ethics; leadership shelf life; succession planning; effective exiting strategies